The Paralogous Genes PDR18 and SNQ2, Encoding Multidrug Resistance ABC Transporters, Derive From a Recent Duplication Event, PDR18 Being Specific to the Saccharomyces Genus - Godinho, Cláudia P.; Dias, Paulo J.; Ponçot, Elise; Sá-Correia, Isabel (Frontiers in Genetics, 2018)
Pleiotropic drug resistance (PDR) family of ATP-binding cassette (ABC) transporters play a key role in the simultaneous acquisition of resistance to a wide range of structurally and functionally unrelated cytotoxic compounds in yeasts. Saccharomyces cerevisiae Pdr18 was proposed to transport ergosterol at the plasma membrane, contributing to the maintenance of adequate ergosterol content and decreased levels of stress-induced membrane disorganization and permeabilization under multistress challenge leading to resistance to ethanol, acetic acid and the herbicide 2,4-D, among other compounds. PDR18 is a paralog of SNQ2, first described as a determinant of resistance to the chemical mutagen 4-NQO. The phylogenetic and neighborhood analysis performed in this work to reconstruct the evolutionary history of ScPDR18 gene in Saccharomycetaceae yeasts was focused on the 214 Pdr18/Snq2 homologs from the genomes of 117 strains belonging to 29 yeast species across that family. Results support the idea that a single duplication event occurring in the common ancestor of the Saccharomyces genus yeasts was at the origin of PDR18 and SNQ2, and that by chromosome translocation PDR18 gained a subtelomeric region location in chromosome XIV. The multidrug/multixenobiotic phenotypic profiles of S. cerevisiae pdr18Δ and snq2Δ deletion mutants were compared, as well as the susceptibility profile for Candida glabrata snq2Δ deletion mutant, given that this yeast species has diverged previously to the duplication event on the origin of PDR18 and SNQ2 genes and encode only one Pdr18/Snq2 homolog. Results show a significant overlap between ScSnq2 and CgSnq2 roles in multidrug/multixenobiotic resistance (MDR/MXR) as well as some overlap in azole resistance between ScPdr18 and CgSnq2. The fact that ScSnq2 and ScPdr18 confer resistance to different sets of chemical compounds with little overlapping is consistent with the subfunctionalization and neofunctionalization of these gene copies. The elucidation of the real biological role of ScSNQ2 will enlighten this issue. Remarkably, PDR18 is only found in Saccharomyces genus genomes and is present in almost all the recently available 1,000 deep coverage genomes of natural S. cerevisiae isolates, consistent with the relevant encoded physiological function.